Artificial pancreas clinical trials: Moving towards closed-loop control using insulin-on-board constraints. (August 2018) - Fushimi, Emilia; Rosales, Nicolás; De Battista, Hernán; Garelli, Fabricio
Highlights: Novel methods are presented that aim to protect T1DM patients from hypoglycemia. Two modes of operations are proposed: the time enable and the amplitude enable. The time enable is designed to work around hybrid controllers. The amplitude enable is meant to be used with fully automatic controllers. Simulations showed that the use of these methods improve the time in normoglycemia. Abstract: Artificial pancreas (AP) systems for people with type 1 diabetes (T1DM) combine the use of a smart insulin pump with a Continuous Glucose Monitor (CGM) and a control algorithm to improve the regulation of glycaemia. Based on the extensive clinical evidence provided by the main research groups in the area, a hybrid control algorithm combining insulin meal boluses and glucose feedback action has been recently approved. However, this sort of algorithms should be refined especially during the postprandial period. In turn, fully closed-loop control strategies have to be further developed. In either case, intensive in vivo validation is necessary to ensure the viability of the proposed strategy as an effective method to treat T1DM patients. In this paper, a safety layer called SAFE loop[1] is reformulated to be employed during clinical trials in two different ways: the time enable mode to gradually activate the closed-loop control after an insulin meal bolus in hybrid configurations; and the amplitude enable mode to activate the full closed-loop control as long as the insulin infusion does not exceed the conventional therapy to a given extent. The SAFE module decides the activation of the controller as a function of a constraint on the insulin on board (IOB). In the case of the Time Enable, this results in the use of a constant restriction on the IOB, whereas in the amplitude enable it results in the use of a time-varying IOB constraint. Both operation modes are evaluated in silico using broadly accepted high-order models and the results contrasted with the ones obtained without the SAFE protection.